(untitled) (Semiárida, 2020)
In predicted sight of selection in a Genetic Development Program is important to know how selection through just one component modifies another correlated with it; mainly negative correlations that can neutralized the breeder’s effort. Direct and indirect contribution of some characters have been evaluated on wheat with the assumption of their association to final grain yield. It was accomplished through a simplified cause-effect model Positive and significant associations have been found between: tillers fertile per plant and yield (0,49**) tillers fertile per plant and height (0,29**), grain per spike and yield (0,25**); tillers fertile and grain per spike (0,24**); spikelets per spike and grain per spike (0,22*); spikelets per spike and yield (0,19*); tillers fertile and spikelets per spike (0,18*); epikelets per spike and height (0,14*) and plant height and yield (0,12*). Tillers fertile and yield showed direct, positive and significant effect (P=0,4452). It resulted independent of spikelets per spike and grain per spike as much as between them. Genetic determination just explained 26,5% of total variation of individual yield in a single plant. A model more complex do not contribute with additional information. It suggested to go deep into this study, including morphological characters.